(untitled) (Sains Humanika, 2014)
Human resource which known as manpower or people in organizations, is important asset for organization sectors such as manufacturing, service and production. It is also a resource that needs to maintain in a competitive business environment nowadays. Managing people in the organization is harder unlike controlling capital, organizational system and technology to ensure an effective management. The organizations need an effective human resource management (HRM) whereby HRM practices could support the organizational functions in order to achieve the organization goals. In this regard, HRM practices are organizational activities that monitor the pool of human resource and confirm that human resource is utilized towards the organizational goals. The main objective of this study is to review the models that have been applied in banking industry in order to build an understanding of HRM practices adopted by that industry. This study employs a qualitative approach by using the library-oriented method. The results indicate the understanding ofÂ human resource management practices framework in banking industry and its implications. Â